Hacia una historia de las tendencias trotskistas después de Trotsky - Gaido, Daniel (Docta Ignorancia, 2022)
The history of Trotskyist tendencies after Trotsky remains, more than 80 years after Trotsky's death, largely terra incognita or, more accurately, a bazaar for all manner of sects to sell their myths. Only once in a while does a work emerge that takes the history of Trotskyism out of the realm of mythology and provides us with the elements we need to reconstruct the actual experience of Trotskyist militants in a given time and place. In this sense, this brief work has no other purpose than to provide a general overview of international experiences linked to Trotskyism in the second half of the 20th century in order to advance in a circumstantial understanding of its history and development.